Determining the Effect of Wood Sawdust and Sand on the Compressive Strength and Water Absorption of Clay Pavers - Hilaire Elenga; Ferland Ngoro-Elenga; Jude Nogelvi Ngakosso Ngolo; Timothée Nsongo; Thomas Tamo Tatietsé (Novel Perspectives of Engineering Research Vol. 4, 2021)
The objective of this study is to assess the influence of wood sawdust and sand on the compressive strength and water absorption of clay pavers. In this work, the authors produced paving bricks by mixing cement-stabilized clay with sawdust from different woods (limba or kambala) and different sands (white or crushed). The mineralogical composition of the clay raw material was determined by X-ray diffraction and showed that its phyllite fraction is essentially constituted by 95% of kaolinite and 5% of smectite and/or chlorite/smectite interstratified. The determination of the compressive strengths gave better strengths for the combinations "clay stabilized with 4% cement mixed with 4% of kambala sawdust and 5% of white sand" and "clay stabilized with 4% cement mixed with 4% of limba sawdust and 5% of crushed sand". The paving bricks had a water absorption rate ranging from 18.1 to 20.4%.